Characterization of Trichoderma reesei cellobiohydrolase Cel7A secreted from Pichia pastoris using two different promoters - Boer, Harry; Teeri, Tuula T.; Koivula, Anu (Biotechnology and bioengineering, 2000)
Heterologous expression of T. reesei cellobiohydrolase Cel7A in a methylotrophic yeast Pichia pastoris was tested both under the P. pastoris alcohol oxidase (AOX1) promoter and the glyceraldehyde‐3‐phosphate dehydrogenase (GAP) promoter in a fermentor. Production of Cel7A with the AOX1 promoter gave a better yield, although part of the enzyme expressed was apparently not correctly folded. Cel7A expressed in P. pastoris is overglycosylated at its N‐glycosylation sites as compared to the native T. reesei protein, but less extensive than Cel7A expressed in Saccharomyces cerevisiae. The kcat and Km values for the purified protein on soluble substrates are similar to the values found for the native Trichoderma Cel7A, whereas the degradation rate on crystalline substrate (BMCC) is somewhat reduced. The measured pH optimum also closely resembles that of purified T. reesei Cel7A. Furthermore, the hyperglycosylation does not affect the thermostability of the enzyme monitored with tryptophane fluorescence and activity measurements. On the other hand, CD measurements indicate that the formation of disulfide bridges is an important step in the correct folding of Cel7A and might explain the difficulties encountered in heterologous expression of T. reesei Cel7A. The constitutive GAP promoter expression system of P. pastoris is nevertheless well suited for activity screening of cellulase activities in microtiter plates. With this type of screening method a faster selection of site‐directed and random mutants with, for instance, an altered optimum pH is possible, in contrast to the homologous T. reesei expression system. © 2000 John Wiley & Sons, Inc. Biotechnol Bioeng 69:486–494, 2000.